Development of powertiller operated Paddy Reaper Windrower - Shiny Lukose (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 1997)
A vertical conveyor reaper-windrower suitable for mounting on KAMCO 9hp powertiller was developed Kerala for the first time. After considering the maneuvrability, weight distribution, field capacity and power transmission, the 1.6m width vertical reaper was selected for the KAMCO powertiller and was locally fabricated. The complete rotavator unit was dismantled and a newly designed power transmission unit was fitted on the KAMCO powertiller. The handle was kept at an ergonomically suitable height of 1m. A combination frame was developed inorder to accommodate both the engine and the reaper at the most appropriate location to achieve the static and dynamic balancing during field operation after the removal of rotavator. The centre of gravity of the engine at the new location was 50mm in front of the wheel axle and at a height of 180mm from its original position. Field evaluation of the reaper was carried out during November and December, 1996 at Tavanur. The front mounted reaper- windrower was evaluated to find out the optimum engine speed and forward speed to achieve better harvesting and windrowing pattern, maximum field capacity and field efficiency with less harvesting losses were found out. For the recommended engine speed of 1200 to 1400rpm at low first and low second gears a forward speed of 0.53 to O. 94m per sec. was obtained in the field. The actual cutting width was 1.5m. The maximum field efficiency of 85 per cent was obtained for first gear when the engine rpm was 1200. Actual field capacity for this speed was 0.224ha per hr. It was seen that for the recommended engine speed between 1200 to 1400rpm a normal forward speed of (.53 to 0. 94m/sec was